New challenges of the public administration towards 200 years of independence - Dill'erva, Italo Felix (2021)
Our country is close to completing 200 years of independence, in a totally atypical year due to a global health emergency; however, Peruvian public administrations are approaching a stage of innovation and continuous improvement in their products and services to meet citizens’ needs. The State as a regulatory and benefit body, has the obligation to modernize its institutions, processes, procedures and public management within state organizations in view of the new challenges of the fourth industrial revolution. An industrial revolution that takes us to the world of the use of technologies, artificial intelligence, the cloud, among other factors that are used with the good institutional progress of Public Administrations, oriented to quality management towards the citizen within a good government that guarantees administrative modernization with the main components of the National Policy for Modernization of Public Management by 2021.